(untitled) (Open Academia: Journal of Scholarly Research, 2025)
Multicyclone dust collectors remain key equipment for capturing particulate matter from high-volume industrial gas streams. This paper develops a hybrid kinetic–dynamic modelling framework that merges a population-balance-based kinetic description with a CFDDPM (Reynolds-averaged Navier–Stokes + Discrete-Particle Model) simulation. The kinetic block describes the exponential decay of dust concentration inside each cyclone cell, whereas the dynamic block resolves gas-phase turbulence, pressure loss and particle drag. Two characteristic curves are presented: (1) collection efficiency versus particle diameter (0.1–10 µm) and (2) the kinetic decay of outlet dust concentration over 60 s. Validation against recent industrial measurements shows prediction errors below 6 % for efficiency and below 4 % for pressure drop, demonstrating that the coupled model is a reliable tool for optimising cell number and diameter when designing industrial air-cleaning systems